2022
DOI: 10.3390/met12111925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basalt Fiber Content on Mechanical and Tribological Properties of Copper-Matrix Composites

Abstract: The basalt-fiber-reinforced copper-matrix composites were fabricated using spark plasma sintering. The effect of basalt fiber content on the mechanical and tribological properties of copper-matrix composites was investigated. The results show that the relative density decreased, the hardness increased and the tensile strength first increased and then decreased with the increase in fiber content. The optimal tensile strength of 276 MPa was obtained when the content of basalt fiber was 1.5 wt.%. The friction coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As a result, its storage modulus diminishes rapidly, as does the amplitude of tan. Whenever the SiO 2 levels are excessive (9 wt%), aggregates on the ber surface impede resin-ber interaction, and interfacial bonding is poor, leading to greater energy dissipation [22].…”
Section: Loss Modulusmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, its storage modulus diminishes rapidly, as does the amplitude of tan. Whenever the SiO 2 levels are excessive (9 wt%), aggregates on the ber surface impede resin-ber interaction, and interfacial bonding is poor, leading to greater energy dissipation [22].…”
Section: Loss Modulusmentioning
confidence: 99%
“…The physical and dielectric characteristics of a carbon ber insulation sheet were enhanced as a result. Cheng et al found that increasing the silica concentration improved the compression strength of glass-epoxy hybrids [22]. The improved strength of concrete might be ascribed to improved interfacial adhesion caused by the scattered silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Composites are captivating because to their light weight, relatively inexpensive, great oxidation resistance, and outstanding hardenability [10][11] . Preponderance of these innovative tasks was influenced by the desire to combat issues with corrosion that metallic materials faced 12). During 1950s these composite structures begin to install in the ship and submarines with the length less than 15 m, while lengths have continuously risen over time, all composite naval ships may now reach lengths of 90 meters.…”
Section: Introductionmentioning
confidence: 99%